This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let L = lim x → 1 x x − 1 1 . We can rewrite L using the exponential in order to make it simpler in the following way
L = x → 1 lim x x − 1 1 = x → 1 lim exp ( x − 1 ln x )
By doing this, we get to the indeterminate form 0 / 0 and it is a simple application of L'Hopital's
L = x → 1 lim exp ( x − 1 ln x ) = x → 1 lim exp ( x 1 ) = exp ( 1 ) = e .
How does this relate to the given problem?
Log in to reply
the question is equivalent to (1+x-1)^(1/(x-1))=(1-(1-x))^(1/(x-1)), then apply the formula
Problem Loading...
Note Loading...
Set Loading...
L = x → 1 lim x x − 1 1 = e lim x → 1 x − 1 1 ( x − 1 ) = e ≈ 2 . 7 1 8 2 8 1 8 2 It is 1 ∞ form, use x → a lim ( g ( x ) f ( x ) ) h ( x ) = e lim x → a h ( x ) ( g ( x ) f ( x ) − 1 )